PENGARUH RASIO KEUANGAN TERHADAPA HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Santika, Tika Tia; Yusran, Rio Rahmat (Aksara Public, 2020)
This study aimed to find the effect of financial ratios on the stock prices. The financial ratios studied are: current ratio, debt to equity ratio, return on assets and price earning ratio. The population in this study were pharmaceutical companies that were listed on the Indonesia Stock Exchange period 2014-2018. The research sample of 7 pharmaceutical companies was obtained by purposive sampling technique. This type of research used in this study is descriptive. The data collection technique used is documentation. Data analysis was performed using multiple linear regression analysis techniques with the help of SPSS 25 software. From the results of the analysis it can be concluded that partially the current ratio, debt to equity ratio and price earning ratio variables didn’t significantly influence the price shares, whilenthe variable return on assets has a significant effect on stock prices. Simultaneously variable current ratio, debt to equity ratio, return on assets and price earning ratio have no significant effect.